Wages or fringes? Some evidence on trade-offs and sorting - Tor Eriksson; Nicolai Kristensen (Institute for the Study of Labor (IZA), 2010)
The two key predictions of hedonic wage theory are that there is a trade-off between wages and nonmonetary rewards and that the latter can be used as a sorting device by firms to attract and retain the kind of employees they desire. Empirical analysis of these topics are scarce as they require detailed data on all monetary as well as nonmonetary rewards, not only for the job chosen but also for alternative offers. In this paper this data predicament is solved by the use of the vignettes method to estimate individuals' willingness to pay for fringe benefits and job amenities. We find clear negative wage-fringe trade-offs, considerable heterogeneity in willingness to pay for fringe benefits, and signs of sorting. The findings imply that personnel economics models can be applied also to the analysis of nonmonetary rewards.
Keywords: J32; J33; M52; 330; fringe benefits; nonmonetary rewards; trade-off; sorting; heterogeneity